Advances in characterization of triacylglycerols: Expansion of materials used in Joint JOCS/AOCS Official Method Ch 3a‐19. (9th May 2022) - Mochizuki, Mamiko; Watanabe, Yomi; Taha, Ameer Y.; Masuyama, Araki
Abstract: Joint JOCS/AOCS Official Method Ch 3a‐19 was an improvement over triacylglycerol characterization methods based on hydrolysis with pancreatic lipase. In this study we developed three further improvements and applied them to the analysis of the fatty acid distribution in triacylglycerols from trout. First, the liquid–liquid extraction of lipid by chloroform and methanol from fish meat was replaced with a single extraction step using pre‐packed columns. This allowed the extraction time to be reduced from 30 min/sample to 5 min/sample with ca . 10% higher yield using half the volume of the extraction solvent, chloroform. Both extraction methods gave similar FA composition of the extracted oil. Furthermore, an alternative CALB lipase and an alternative normal‐phase solid phase extraction column were shown to reliably duplicate the results obtained with the Official Method Ch 3a‐19. In addition, the SPE columns could be used at least 5 times without loss of separation and without carryover.